2023
DOI: 10.3389/fimmu.2023.1144774
|View full text |Cite
|
Sign up to set email alerts
|

LRPPRC facilitates tumor progression and immune evasion through upregulation of m6A modification of PD-L1 mRNA in hepatocellular carcinoma

Abstract: ObjectiveLRPPRC is a newly discovered N6-methyladenosine (m6A) modification reader, which potentially affects hepatocellular carcinoma (HCC) progression. PD-L1 in tumor cells is essential for tumor immune evasion. This work investigated the LRPPRC-mediated m6A-modification effect on PD-L1 mRNA and immune escape in HCC.MethodsExpression and clinical implication of LRPPRC and PD-L1 were measured in human HCC cohorts. The influence of LRPPRC on malignant behaviors of HCC cells was investigated through in vitro as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Notably, this inhibition appears to post-transcriptionally amplify PD-L1, perhaps through an m6A-dependent process, thus enhancing the mRNA stability of PD-L1. Such findings illuminate a fresh avenue by which m6A regulators might facilitate immunosuppression in hepatocellular carcinoma [48]. Further delving into its molecular pathways, LRPPRC supports both Yap-P27-driven cell polyploidy and P62-HDAC6-guided autophagy maturation.…”
Section: Discussionmentioning
confidence: 75%
“…Notably, this inhibition appears to post-transcriptionally amplify PD-L1, perhaps through an m6A-dependent process, thus enhancing the mRNA stability of PD-L1. Such findings illuminate a fresh avenue by which m6A regulators might facilitate immunosuppression in hepatocellular carcinoma [48]. Further delving into its molecular pathways, LRPPRC supports both Yap-P27-driven cell polyploidy and P62-HDAC6-guided autophagy maturation.…”
Section: Discussionmentioning
confidence: 75%
“… 31 , 32 Recent studies have shown that LRPPRC upregulates Programmed Death Ligand 1 (PD‐L1) expression by increasing the stability of PD‐L1 mRNA in an m 6 A‐dependent manner. 33 In this regard, LRPPRC acts as a cytoplasmic m 6 A reader protein that also promotes the stability of LDHA and WDR76 mRNA in an m 6 A‐dependent manner. We further examined LDHA and identified the LRPPRC–m 6 A–LDHA axis as a critical molecular signalling pathway involved in LRPPRC‐mediated tumourigenesis and metastasis of TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…However, its impact on HCC remains unexplored. LRPPRC, involved in mitochondrial oxidative phosphorylation, exhibits signi cant upregulation in HCC tissues and is associated with advanced stages and poor overall and disease-free survival [14,15]. Inactivation of LRPPRC with GYS1 acts in concert with glucose starvation to induce disul dptosis [5].…”
Section: Discussionmentioning
confidence: 99%